1996
DOI: 10.1007/bf01623387
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound velocity and broadband attenuation over a wide range of bone mineral density

Abstract: Ultrasound velocity (UV) and broadband ultrasound attenuation (BUA) were studied in human and bovine bone with a wide range of bone mineral density (BMD). The BMD of 98 fresh specimens was measured by quantitative computed tomography: 42 cancellous specimens from women in the age group of 64 +/- 4 years; 51 bovine cancellous and 5 bovine cortical. BMD values ranged from 90 to 400 mg/cm3 for the human cancellous bone, 310 to 870 mg/cm3 for the bovine cancellous bone, and 1750 to 1780 mg/cm3 for the bovine corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 28 publications
11
41
0
1
Order By: Relevance
“…These results are also consistent with findings by previous authors investigating the relationships of the nBUA and the backscatter coefficient with the bone density in trabecular bone in vitro. [27][28][29][30] For instance, Serpe and Rho reported that the dependence of the nBUA on the apparent bone density was nonlinear with a downwardly inflected parabola shape when covering a wide range of densities from 130 and 913 mg cm À3 in 22 bovine tibial trabecular bone samples. 28 Apostolopoulos and Deligianni found a nonlinear relationship between the backscatter coefficient at 0.8 MHz and the apparent bone density over a range of densities from 306 to 969 mg cm À3 in 40 bovine femoral trabecular bone samples.…”
Section: Resultsmentioning
confidence: 99%
“…These results are also consistent with findings by previous authors investigating the relationships of the nBUA and the backscatter coefficient with the bone density in trabecular bone in vitro. [27][28][29][30] For instance, Serpe and Rho reported that the dependence of the nBUA on the apparent bone density was nonlinear with a downwardly inflected parabola shape when covering a wide range of densities from 130 and 913 mg cm À3 in 22 bovine tibial trabecular bone samples. 28 Apostolopoulos and Deligianni found a nonlinear relationship between the backscatter coefficient at 0.8 MHz and the apparent bone density over a range of densities from 306 to 969 mg cm À3 in 40 bovine femoral trabecular bone samples.…”
Section: Resultsmentioning
confidence: 99%
“…US attenuation and velocity in bone are affected not only by mineral content but also by other material and structural properties of the bone. The velocity of ultrasound is reported to correlated with the density and elasticity of a material, while BUA is dependent on its structural characteristics [9,[24][25][26][27].…”
Section: Biological Significance Of Sos and Buamentioning
confidence: 99%
“…[8][9][10][11][12] Ultrasound attenuation is the energy loss during its propagation through the medium. It is mainly caused by the acoustic scattering from the porous trabecular structure and the heat dissipation due to the viscosity of the bone.…”
Section: Introductionmentioning
confidence: 99%